Patterns of nutrient transfer in lowland catchments : A case study from northeastern Europe - Mourad, D.S.J. (Utrecht University, Royal Dutch Geographical Society, 2008)
Although nitrogen (N) and phosphorus (P) emissions from agricultural diffuse sources and point emissions decreased dramatically after the political and economic changes in northeastern Europe in the beginning of the 1990s, the reaction of stream water quality is often limited or absent. This holds in particular for the surface waters in the drainage basin of Lake Peipsi/Chudskoe, a large (3555 km2) and shallow (mean depth: 7.1 m) lake on the border of Estonia and Russia. This lake is still suffering from eutrophication phenomena such as algal blooms due to N and P input from the drainage basin. The general aim of the research described in this thesis was to identify and quantify the controls on the transfer of the N and P in northeastern European lowland catchments. I focussed on the drainage basin of Lake Peipsi/Chudskoe (size: 45541 km2), and on the pilot catchment of the Ahja Jõgi (Ahja River; 901 km2) in particular. In chapter 3, past (1985-1999) and possible future changes (up to 2019) of total N (Ntot) and total P (P) emissions as a result of economic changes were simulated for five year periods and for the entire Lake Peipsi/Chudskoe drainage basin. The impact of these changes on Ntot and Ptot inputs into the lake was assessed using a drainage basin scale GIS-model. In chapter 4, for the pilot catchment of the Ahja River, spatial and seasonal variability of Dissolved Inorganic Nitrogen (DIN) and Dissolved Reactive Phosphorus (DRP) concentrations was assessed based on the results of six stream sampling campaigns. Because hydrology and hydrological connectivity is so important for the spatial and temporal distribution of nutrient concentrations, a novel GIS-based hydrological model was developed, to simulate quick and slow hydrological pathways and groundwater transit times (chapter 5). The influence of these hydrological pathways on DIN concentrations was quantified by 1) comparing the average 1991-2000 relative contribution of groundwater with a short (12-50 year) transit time to typical summer baseflow (summer 2002) in-stream DIN concentrations, and 2) the relative contribution of quick flow from agricultural areas with typical spring flood (spring 2004) in-stream DIN concentrations. Finally, a novel combination of existing models was used to quantify the spatio-temporal dynamics of nitrogen emissions, transfer pathways, and in-stream retention in the Ahja River catchment between 1991 and 2004 (chapter 6). I conclude that the key factors controlling nutrient transfer are the magnitude of diffuse emissions from agriculture, the magnitude of point emissions in the case of P, the magnitude of total runoff, the spatial and temporal distribution of hydrological pathways, the amount of nutrients that is stored in soil and groundwater, and in-stream retention. With this information, a conceptual model for the transfer of nutrients in lowland catchments emerges. On basis of this conceptual model, the sensitivity of nutrient transfer to emission and climate change can be assessed.
Keywords: Agriculture; connectivity; Estonia; GIS; groundwater transit times; Lake Peipsi/Chudskoe; modelling; nitrogen; phosphorus; retention; water quality